Allergenicity of Deamidated and/or Peptide-Bond-Hydrolyzed Wheat Gliadin by Transdermal Administration - Abe, Ryosuke (Foods, 2020)
Hydrochloric acid (HCl)-treated wheat protein (HWP) is widely used in various products, including foods, cosmetics and shampoos. Recently, immediate hypersensitivity towards facial soap containing HWP has been reported. HCl treatment of protein causes hydrolysis not only of main-chain amide bonds (peptide-bond hydrolysis) but also of side-chain ones (deamidation). We have already reported that gliadin, the main allergen in wheat, reduces allergenicity and increases digestibility by deamidation, indicating that deamidation and peptide-bond hydrolysis are effective to reduce the allergenicity of wheat protein. However, transdermally administered HWP is assumed to induce sensitization to orally administered wheat protein even in those who have been taking wheat products daily before sensitization. The present study was conducted to examine which structural change is responsible for the induction of cutaneous sensitization by comparing the allergenicity of deamidated and/or peptide-bond-hydrolyzed wheat gliadin. Because we have developed a deamidation method without causing peptide-bond hydrolysis, only deamidated wheat gliadin is available. Therefore, after deamidated-only, hydrolyzed-only, and deamidated and hydrolyzed gliadins were transdermally administered to mice for several weeks, the corresponding gliadin was intraperitoneally administered and allergenicity was evaluated. Transdermal administration of deamidated and hydrolyzed gliadin induced severe allergic reaction, while that of deamidated-only and hydrolyzed-only gliadin showed almost no allergic response. This result indicates that both deamidation and peptide-bond hydrolysis are necessary to increase the allergenic potency of transdermally administered wheat gliadin.